Visual Representations to Stimulate New Musicking Strategies in Live Coding. - Masu, Raul; Dal Rì, Francesco Ardan (Organised Sound, 2023)
In live coding, the code can be considered as an archetypal form of score that notates formal processes. We aimed at investigating the possibility of using graphic visuals as a complementary form of descriptive score by visualising sound events using different time representations. To this end, we devised two visualisation systems (Time_X and Time_Z). Time_X represents time along the x -axis, while in Time_Z the objects overlap along an imaginary z -axis. Based on our previous personal experience with the system, such forms of visual scores can help to develop new musicking strategies while live coding. In this article, we wanted to broaden such reflections, and we used them as probes in a study with three live coders. After tailoring the two systems to the usual practice of the three participants, we asked them to use the systems for three weeks and keep a diary. At the end, we interviewed them. Based on their comments, we present some reflections on the use of graphic forms of visualisation in live coding, on how they can support musicking process, and to what extent such visuals can be considered scores.